DETEKSI DINI GANGGUAN METABOLISME GLUKOSA - Tirtasari, Silviana; Nugroho, Dodo; Tjunaity, Stefany (Jurnal Serina Abdimas, 2024)
Diabetes Mellitus is the cause of 1.5 million deaths, and 48% of all diabetes-related deaths occur in individuals under the age of 70. Monitoring blood glucose levels is a crucial part of preventive measures against diabetes mellitus. Many people are unaware of their blood sugar levels due to laziness and a belief that it is not important, as diabetes mellitus often shows no symptoms. Partners in this activity rarely undergo blood glucose checks due to their busy schedules and a perception that checking blood sugar levels is unnecessary when no symptoms of diabetes mellitus are present. Blood glucose testing is the initial step in early detection of diabetes mellitus and raising awareness about the importance of regulating blood sugar levels in partners. Based on the issues with the partners, the objective of the health service team from FK UNTAR is to increase awareness of blood glucose testing for early detection of diabetes mellitus. A total of 23 educators underwent testing. The fasting blood glucose results revealed that 17.4% of participants had levels in the range of 100-125 mg/dL, and 4.3% had levels ≥ 126 mg/dL (due to a history of diabetes). This activity was carried out as an early detection effort to prevent the development of diabetes mellitus in the future. Therefore, further activities are needed to assist educators with results falling into the prediabetes category, encouraging preventive measures to avoid the progression to diabetes mellitus, and for those with high results, immediate consultation with a doctor for further management.